Charactarization of a nitrate responsive MYB transcription factor in Arabidopsis - Stoerger, Vincent, author; Bush, Daniel, advisor; Bedinger, Patricia, committee member; Byrne, Patrick, committee member; Reddy, A. S. N., committee member (Colorado State University. Libraries, 2013)
NRM1 (AT1g13300) is a gene that was initially uncovered in a microarray experiment where Arabidopsis was starved of nitrate and then re-fed varying concentrations of nitrate. NRM1 was one of a few genes that was up-regulated in all treatments. NRM1 has a single MYB like domain and a leucine-zipper like domain. We hypothesized that NRM1 is a transcription factor that plays a role in the plants response to nitrate availability.

NRM1-GFP fusions showed that NRM1 was localized to the nucleus of the cell. We did not see any evidence of differential localization of NRM1 when examining its location under changing levels of nitrate availability. The yeast two hybrid system was utilized to test if NRM1 interacts with itself to form a homodimer or with another protein to form a heterodimer that would contain the two MYB domains needed for specific DNA binding. No protein - protein interactions were found in our experiments nor are there reports of NRM1 interactions in publicly available databases of interactions.

Recombinant expression plasmids containing NRM1 have been constructed and the protein expression has been examined. Purification of recombinant protein was successful but purity of the product needs to be improved. Once the pure protein is obtained, antibodies will be made and chromatin immuno precipitation experiments can be performed.

Experiments performed with NRM1 promoter

NRM1 is part of a family of genes that contains two closely related genes NRM2 and MRM3. NRM3 is most similar to NRM1 and has a similar expression profile. NMR2 is slightly less similar and is expressed throughout the plant. To determine what role NRM1 might play in root architecture, NRM1-NRM2 double mutants, NRM1 overexpressors and NRM1-NRM3 microRNA plants were made. NRM1-NRM2 double mutant plants showed shorter primary roots than wild type plants when grown on low nitrate media. These plants also produced fewer lateral roots when grown on complete, low nitrate and low phosphate media. Plants overexpressing NRM1 showed differences in root architecture but these changes were not consistent between lines. Further experiments will need to be performed to deduce exactly how these changes in root architecture are related to the function of NRM1. NRM1-NRM3 microRNA plants are being produced, but are not ready for analysis at this point in time.

Some evidence that NRM1 is a transcription factor and is involved in the root architecture response to nitrate has been uncovered and several tools to further explore its function have been developed.